Network Design Planning for Very Small Aperture Terminal (VSAT) in Nagari Rangkiang Luluih, Solok Regency - Saputra, Roni; Septima, Uzma; Setiawan, Herry (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2024)
The public truly needs technological advancements, particularly internet networks, in order to access information such as phone, data, and video services, all of which are growing in volume. This requirement also holds true for isolated places without internet connectivity, like Nagari Rangkiang Luluih. The primary barrier to building telecommunications infrastructure, such as Base Transceiver Stations (BTS), which are more expensive than BTS, is geographic conditions. For isolated Indonesian locations without access to a telecommunications network, such as Rangkiang Luluih, VSAT technology offers a practical alternative in the form of dependable and constant internet connections. VSAT provides greater coverage and increased dependability by acting as a repeater for satellite communications. greater than BTS, particularly in regions with challenging topography. When compared to BTS technology, the design findings demonstrate that VSAT is a more cost-effective and efficient option. Planning the VSAT network design in Nagari Rangkiang Luluih yielded optimal parameter values for internet access services in the Tigo Lurah District, Solok Regency, and the hilly, forested, and valleyous remote areas. These values included an average delay of 34.08 ms, a throughput of 379.66 bps, a jitter of 10.58 ms, and a packet loss of 0%.